Is a higher altitude associated with shorter survival among at-risk neonates? - Dueñas-Espín, Iván; Armijos-Acurio, Luciana; Espín, Estefanía; Espinosa-Herrera, Fernando; Jimbo, Ruth; León Cáceres, Ángela; Nasre-Nasser, Raif; Rivadeneira, María F.; Rojas-Rueda, David; Ruiz-Cedeño, Laura; Tello, Betzabé; Vásconez-Romero, Daniela (PLOS ONE, 2021)
Introduction We hypothesize that high altitudes could have an adverse effect on neonatal health outcomes, especially among at-risk neonates. The current study aims to assess the association between higher altitudes on survival time among at-risk neonates. Methods Retrospective survival analysis. Setting: Ecuadorian neonates who died at ≤28 days of life. Patients: We analyzed the nationwide dataset of neonatal deaths from the Surveillance System of Neonatal Mortality of the Ministry of Public Health of Ecuador, registered from 126 public and private health care facilities, between January 2014 to September 2017. Main outcome measures: We retrospectively reviewed 3016 patients. We performed a survival analysis by setting the survival time in days as the primary outcome and fixed and mixed-effects Cox proportional hazards models to estimate hazard ratios (HR) for each altitude stratum of each one of the health care facilities in which those neonates were attended, adjusting by individual variables (i.e., birth weight, gestational age at birth, Apgar scale at 5 minutes, and comorbidities); and contextual variables (i.e., administrative planning areas, type of health care facility, and level of care). Results Altitudes of health care facilities ranging from 80 to <2500 m, 2500 to <2750m, and ≥2750 m were associated respectively with 20% (95% CI: 1% to 44%), 32% (95% CI:<1% to 79%) and 37% (95% CI: 8% to 75%) increased HR; compared with altitudes at <80 m. Conclusion Higher altitudes are independently associated with shorter survival time, as measured by days among at-risk neonates. Altitude should be considered when assessing the risk of having negative health outcomes during neonatal period.